Long-term participation 7-8 years after stroke: Experiences of people in working-age - Törnbom, Karin; Lundälv, Jörgen; Sunnerhagen, Katharina S. (PLOS ONE, 2019)
Objective To enhance the understanding of long-term participation in working-aged people 7–8 years after stroke. Methods This study had a qualitative design, using a thematic analysis methodology. Eleven individuals took part in an in depth interview 7–8 years after a first time stroke. They had received care at the Sahlgrenska University Hospital in Gothenburg, and were recruited as a heterogenic sample with respect to age, gender, stroke severity and subtype. Results From the participants’ experiences four themes emerged: “Returning to work after stroke”; “Working life 7–8 years after stroke”; “Social life 7–8 years after stroke”; and “A state of reorientation in life”. Quotes about experienced participation in everyday life were summarized and presented as “Participation after stroke narratives”. Participants chose to emphasize on work- and social life when describing situations of successful participation. Being included in the wider community and having a sense of purpose, when interacting with others, were factors that these narratives had in common. Participants had gradually become accustomed to a somewhat altered life situation. Some consequences after stroke were still considered frustrating in social or work situations. However, the importance of these issues had reduced and were no longer problematized. Conclusions Participants felt content with their everyday life in general, which was a principal and positive result of this study. Reaching a stage of acceptance seemed to be a complex and continuous struggle, and an individual approach in long-term rehabilitation would be valuable to support this personal process. More knowledge about what factors that facilitate participation in people of working-age many years after stroke is needed, so that more people can reach a state of positive identity and participation.